Need for an Ethical Approach to Education in Medicine - Ortiz Cabanillas, Pedro (2001)
A moral characterization of the School of Medicine as an educational institution responsible of the professional formation of physicians was carried out. As a result, certain flows of the educational process that are not certainly the teaching – learning procedures but depend on an inadequate conceptualization of man’s nature, especially about what the process of the personality in formation is were identified. Therefore, the need to apply an ethical theory and a model of personality moral development oriented towards the moralization of society as the base of a more consequent medical education regarding the health needs of developing countries as ours has come forth.